Incidencia de la aplicación de la NIIF 16 “propiedad planta y equipo” en el sector bancario de la ciudad de Guaranda año 2016. - García Guillín, Alvaro Jhoney (2016)
The High complexity that entails the application of international accounting standards in the operations of the institutions and the advanced development of the same, has led to many countries, including Ecuador, through the Superintendency of companies, to adopt international accounting standards. In the city of Guaranda, there are five banks that are the basis of this research, the process of transition of the Ecuadorian accounting standards (NEC) to the International's financial reporting standards (IFRS) the banking sector had several drawbacks to incorporate them since this standard represents a total asset of an institution significant percentage, for this reason it is important to conduct an assessment to the movements that will have , with the application of international accounting standards (IFRS). This research work is developed with the theme "impact of the implementation of the IFRS 16"PROPERTY PLANT and EQUIPMENT" in the banking sector of the city of Guaranda year 2016" in order to demonstrate how it affected and as evidenced their need in the banking sector of the city of Guaranda, this applies to the scientific method by which to achieve the acquisition organization or systematization and expression or exhibition of knowledge, as well as field research and documentary research due to coexistence with the object of study. In this research that intends to use qualitative research because of the quality of the activities, relationships, Affairs, media, materials or instruments in a given situation or problem. In the case of this investigation will take as it shows the entire population due to the fact that we will focus on the administrative and financial area consisting of 32 officials.